EFFECT OF DIRECT-TO-CONSUMER ADVERTISING (DTCA) ON STATIN USE IN THE UNITED STATES - Chang, Hsien-Yen (Med Care, 2017)
IMPORTANCE: The value of direct-to-consumer advertising (DTCA) of prescription drugs is widely debated, as is the effect of DTCA on prescription sales and health care utilization. OBJECTIVE: We examined the association between DTCA intensity for statin medications and prescription sales and cholesterol-related health care utilization. DESIGN, SETTING AND PARTICIPANTS: We conducted an ecological study for 75 designated market areas (DMAs) from 2005 to 2009 in the United States using linked data regarding televised DTCA volume; non-DTCA marketing and promotion; retail, mail order and long-term care prescription drug sales; prescription drug and ambulatory care health care utilization; and contextual factors such as health care density and socioeconomic status. Main outcomes and measures were volume of sales; number of dispensed prescriptions; and high cholesterol-related outpatient visits. Analyses were conducted in 2016. RESULTS: The intensity of rosuvastatin and atorvastatin ad exposures per household varied substantially across DMAs. After adjustment for socioeconomic, demographic and clinical characteristics, each 100-unit increase in advertisement viewership was associated with a 2.22% (95% confidence interval [CI] 0.30 to 4.19%) increase in statin sales. Similar patterns were observed between DTCA and statin dispensing among the commercially insured. DTCA was associated with increases in high cholesterol-related outpatient visits among adults 18–45 years of age (3.15% increase in visits per 100-unit increase in viewership, 95% CI: 0.98 to 5.37%) but not among those 46–65 years of age (0.51%, 95% CI: −1.49 to 2.55%). CONCLUSION: DTCA for statins is associated with increases in statin utilization and hyperlipidemia-related outpatient visits, especially for young adults.